EMS Provider Compliance with Infection Control Recommendations Is Suboptimal. (3rd April 2014) - Bledsoe, Bryan E.; Sweeney, Richard J.; Berkeley, Ross P.; Cole, Korey T.; Forred, Wesley J.; Johnson, Larry D.
Abstract Introduction. Standard precautions are disease transmission prevention strategies recommended by both the World Health Organization (WHO) and by the Centers for Disease Control and Prevention (CDC). Emergency medical services (EMS) personnel are expected to utilize standard precautions. Methods. This was a prospective observational study of the use of standard precautions by EMS providers arriving at a large urban emergency department (ED). Research assistants (RAs) observed EMS crews throughout their arrival and delivery of patients and recorded data related to the use of gloves, hand hygiene, and equipment disinfection. Results. A total of 423 EMS deliveries were observed, allowing for observation of 899 EMS providers. Only 512 (56.9%) EMS providers arrived wearing gloves. Hand washing was observed in 250 (27.8%) of providers. Reusable equipment disinfection was noted in only 31.6% of opportunities. The most commonly disinfected item was the stretcher (55%). Conclusion. EMS provider compliance with standard precautions and equipment disinfection recommendations is suboptimal. Strategies must be developed to improve EMS provider compliance with internationally recognized infection control guidelines. Key words: Emergency medical services, hand washing, hygiene, disinfection, disease prevention